Assessment of Water Quality of Kodiat Rosfa Dam and Suitability For Consumption and Irrigation (Algeria) - Chellali Rachid (Al-Qadisiyah Journal For Agriculture Sciences, 2021)
The approach adopted for the assessment of Kodiat Rosfa dam water quality, through the respective indexes WQI and IWQI, allowed to highlight the quality of its waters for the intended uses. Indeed, the physicochemical analyzes of the months of February, March, July and December, corresponding to the monthly precipitation and regularized volumes of 2013, 2014, 2015 selected,  revealed that 08 samples out of 12 have a WQI within 50 to 100, and 04 samples with WQI lower than 50. This classified the dam waters as good to excellent for consumption. Nevertheless, the results of IWQI index used to assess the quality of dam water Kodiat Rosfa for irrigation show that 7 samples out of 12 present an IWQI within 55 to 70 and 5 samples with IWQI lower than 55. These waters are characterized by moderate (MR) to high (HR) restriction.